EFEK HESPERIDIN DALAM PENINGKATAN AKTIVITAS SITOTOKSIK DOXORUBICIN PADA SEL KANKER LEHER RAHIM HeLa MELALUI MODULASI SIKLUS SEL DAN PEMACUAN APOPTOSIS - , INDRI KUSHARYANTI, S.Farm, APT, Prof. Dr. Edy Meiyanto, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Combination of chemotherapeutic agent and chemopreventive agent is being a new approach in cancer treatment. This is aimed at enhancing the effectivity and also reducing drug resistance and adverse side effect of the chemotherapeutic agent. Hesperidin, a citrus flavonoid has been reported to reduce the proliferation of many cancer cells. The objectives of this study were to investigate cytotoxic activities, cell cycle modulation and apoptosis induction of hesperidin and its combination with doxorubicin on Hela cell lines. MTT [3-(4,5- dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide] assay was used to measure the growth inhibitory effect of hesperidin and its combination with doxorubicin on Hela cells. Cell cycle profile was determined by flowcytometry and the data obtained was analyzed by using ModFit LT 3.0 program. Apoptosis assay was done using double staining method using ethidium-bromide and acridine-orange. Hesperidin inhibited cell growth with IC50 48 Î¼M, while the IC50 of doxorubicin was 1 Î¼M. Combination of 5 Î¼M doxorubicin and 6 Î¼M hesperidin showed strongest inhibitory effect toward Hela cells which save 3,28% of cell viability. Hesperidin of 24 ÂµM accumulated HeLa cells at G1 phase, while doxorubicin of 5 Î¼M accumulated HeLa cells at S phase. Combination of 24 Î¼M hesperidin with 5 Î¼M doxorubicin gave G1 and S phase accumulation at 24 h incubation. All of Hesperidin and Doxorubicin were capable of inducing apoptosis. Their combination increased apoptosis of HeLa sel compared with single treatment. In accordance of this apoptosis induction effect, imunocytochemistry method was conduct to determine the level of Bcl-2 and Bax expression. It is showed that hesperidin, doxorubicin and their combination decreases the expression Bcl-2 and increases the expression of Bax. According to this results, hesperidin has a potency to be developed as co-chemotherapeutic agent for cervical cancer.